Animations and static pictures: The influence of prompting and time of testing. (December 2018) - Kühl, Tim; Navratil, Sabrina D.; Münzer, Stefan
Abstract: Static pictures have an informational disadvantage for dynamic processes compared to animations. It was investigated whether this disadvantage can be compensated by prompting learners to process the specific dynamic information. It was assumed that this processing would lead to a longer lasting knowledge representation. A 2 x 2 x 2 between-subject design with visualization format (static picture vs. animation), prompt (present vs. absent) and time of testing (immediate vs. after one week) was utilized ( N = 263). Participants performed better on test questions about the dynamic information after learning with the animation compared to the static picture. Prompting learners led to higher perceived difficulty, less overconfidence and better performance in a factual knowledge test addressing the prompted information. The quality of the answers to the prompts mediated the knowledge differences between visualization conditions. However, prompts did not compensate for the informational disadvantage of static pictures, irrespective of time of testing. Highlights: Animations led to better performance in a transfer task than static pictures. Prompting learners to process specific content improved knowledge for this content. Performance in answering prompts mediated the superiority of animations. Prompts did not moderate learning with animations compared to static pictures. Time of testing had an impact on factual knowledge, but not on transfer.